PENGARUH KEMUDAHAN AKSES DAN DISKON TERHADAP KEPUTUSAN PEMBELIAN PADA SITUS ONLINE TIKET.COM - Nindy Riska Amalia; Saryadi Saryadi (Universitas Diponegoro, 2018)
The development of business that is getting ahead is always in tandem with technological developments that increasingly rapidly. One business that is influenced by the development of internet technology is e-commerce. As an initiator, Tiket.com has lost competitiveness with emerging competitors. Therefore, the effort to attract consumers to buy is important so that consumers do not switch to other services. This study aims to determine the effect of ease of access and discount on purchasing decisions Tiket.com online site. This research is an explanatory research by using questionnaire as its instrument. Population and sample used are the users of Tiket.com at Diponegoro University taken as many as 156 respondents by using purposive sampling method. Based on the analysis results can be concluded that the ease of access and discounts affect the purchase decision, evidenced through simple linear regression test with regression value of ease of access is equal to 0.461 and a discount is equal to 0.596. The data analysis techniques are using correlation test, determination test, simple linear regression test, multiple linear regression test, t test and F test with the help of program SPSS (Statistical Product and Service Solutions) version 23. The effect of ease of access and discount are together to influence purchase decision of 43.8%. While the remaining 56.2% influenced by other factors. Based on the results of the research, the author can provide advices to Tiket.com such as to improve the user interface both on the site and mobile application in order to be much easier, more attention to price competition and features with competitors as a comparative material, and review the standard operating procedure related to payment and reservation procedures.